Predictive and Prognostic Assessment Models for Tumor Deposit in Colorectal Cancer Patients With No Distant Metastasis - Chen, Jingyu; Zhang, Zizhen; Ni, Jiaojiao; Sun, Jiawei; Ren, Wenhao; Shen, Yan; Shi, Liuhong; Xue, Meng (Frontiers in Oncology, 2022)
ABSTRACT Background: More and more evidence indicated that tumor deposit (TD) was significantly associated with local recurrence, distant metastasis (DM) and poor prognosis for patients with colorectal cancer (CRC). This study aims to explore the main clinical risk factors for the presence of TD in CRC patients with no distant metastasis (CRC-NDM) and the prognostic factors for the TD-positive patients after surgery. Methods: The data of patients with CRC-NDM between 2010 and 2017 was extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Logistic regression model was used to identify risk factors for TD presence. Fine and Gray’s competing-risk model was performed to analyze prognostic factors for TD-positive CRC-NDM patients. A predictive nomogram was constructed using the multivariate logistic regression model. The concordance index (C-index), the area under receiver operating characteristic (ROC) curve (AUC) and the calibration were used to evaluate the predictive nomogram. Also, a prognostic nomogram was built based on multivariate competing-risk regression. C-index, the calibration and decision-curve analysis (DCA) were performed to validate the prognostic model. Results: The predictive nomogram to predict the presence of TD had a C-index of 0.785, AUC of 0.787 and 0.782 in the training and validation sets, respectively. From the competing-risk analysis, chemotherapy (SHR = 0.542, P<0.001) can significantly reduce the colorectal cancer specific death (CCSD). The prognostic nomogram for the outcome prediction in postoperative CRC-NDM patients with TD had a C-index of 0.727. The 5-year survival of CCSD was 17.16%, 36.20% and 63.19% in low-, medium-, and high-risk subgroups respectively (Gray’s test, p < 0.001). Conclusions: We constructed an easily predictive nomogram in identifying the high-risk TD-positive CRC-NDM patients. Besides, a prognostic nomogram was built to help clinicians to identify poor outcome individual in postoperative CRC-NDM patients with TD. For the high-risk or medium-risk subgroup, additional chemotherapy and may be more advantageous for the TD-positive patients rather than radiotherapy.